Determinants of perceived service quality in UUM Parcel Center (UPC): A study on the perception of courier service quality among UUM undergraduate students - Anis Syamimi, Mohd Azlan (2020)
Nowadays, most of the institutions of higher education in Malaysia have developed the service which linked to the courier services, notably for students and other university’s citizens. Therefore, the establishment of UniStorage has been initiated to the universities in Malaysia as one of the initiatives for students to receive their parcels. Universiti Utara Malaysia which located at the northern part of the Malaysia peninsula has been selected as a research area in this study. Besides, this study aims to determine the relationship between the independent variables which chiefly include perception of timeliness, order accuracy, information quality, and personnel quality of courier service at UUM Parcel Center (UPC) with its perceived service quality among undergraduate students in UUM Sintok, Kedah as a dependent variable. A total of 377 undergraduate students in UUM Sintok were responding to this study. Throughout this study, a statistical tool called Statistical Package for the Social Science (SPSS) version 23 was used to analyze the collected data. Hence, descriptive statistics, sample T-Test, one-way ANOVA, Pearson correlation, and multiple linear regressions were applied to this study as well. The results of this study were clearly shown that the independent variables (timeliness, order accuracy, information quality, and personnel quality) had a positive impact on the dependent variable (perceived service quality) and besides, influence the level of customers‟ satisfaction as well. Also, it suggested for future research to conduct this similar study to be extended to determine other determinants factor that influence perceived service quality in the courier service industry.